MO439: Cardiovascular Mortality Among Persons With Advanced Chronic Kidney Disease: A Matched Cohort Study. (3rd May 2022) - Kofod, Dea; Carlson, Nicholas; Linnea Freese Ballegaard, Ellen; Torp, Christian; Gislason, Gunnar; Peter Almdal, Thomas; Feldt-Rasmussen, Bo; Hornum, Mads
Abstract: BACKGROUND AND AIMS: Chronic kidney disease (CKD) and diabetes are both well-established risk factors for cardiovascular mortality. However, the risk of cardiovascular mortality and the impact of diabetes for those who have already reached advanced CKD are poorly examined. We examined the risk of cardiovascular mortality among persons with advanced CKD with and without diabetes. METHOD: In a nationwide registry-based retrospective matched cohort study, we identified all Danish persons aged ≥ 18 years with advanced CKD between 2002 and 2018. Persons were included in the study at first measured estimated glomerular filtration rate (eGFR) < 30 mL/min/1.73 m 2 . We excluded persons having a major cardiovascular event or dying < 30 days after inclusion. Non-exposed persons with eGFR ≥ 30 mL/min/1.73m 2 (with and without diabetes) were matched on birthyear and sex in a ratio of 4:1. By using the Danish Register of Medicinal Product Statistics, persons with diabetes were identified. Information regarding mortality was obtained from the Danish Registry of Causes of Death. Multiple outcome-specific Cox regression was performed to calculate average treatment effects as standardized absolute risk of cardiovascular mortality adjusted for age, sex and prior cardiovascular disease and subsequently stratified by age group (18–49, 50–59, 60–69, 70–79, 80 years or older). RESULTS: We included 135 824 persons with advanced CKD. Overall, 52% were women and the mean age was 76 years. There were 31 991 (23.6%) with diabetes, of whom 2512 (7.9%) had type 1 diabetes. The mean duration of diabetes was 9.7 years. Figure 1 depicts the standardized absolute risk of cardiovascular mortality. Estimations stratified by age groups are shown in Table 1 . For persons with diabetes, the standardized absolute risk (95% CI) of cardiovascular mortality was 13.4% (11.5–15.1) in persons aged 18–49 years 5 years after diagnosis, rising to 35.7% (34.7–36.6) in persons aged ≥ 80 years. Compared with age- and sex matched persons, the corresponding relative risk [95% confidence interval (CI)] was 38.0 (29.9–48.1) in persons aged 18–49 years, declining to 1.8 (1.7–1.8) in persons aged ≥ 80 years. Among persons without diabetes, the standardized absolute risk (95% CI) 5 years after diagnosis was 5.2% (4.5–5.8) in persons aged 18–49 years, rising to 33.6% (33.1–34.0) in persons aged ≥ 80 years. The corresponding relative risk was 14.6 (11.7–18.4) and 1.7 (1.6–1.7), respectively, compared with matched persons. Comparing persons with diabetes to persons without diabetes, the relative risk (95% CI) of cardiovascular mortality 5 years after diagnosis was 2.6 (2.2–3.2), 1.8 (1.6–2.9), 1.4 (1.3–1.5), 1.2 (1.1–1.2), 1.1 (1.0–1.1) for age group 18–49, 50–59, 60–69, 70–79, ≥80 years, respectively. CONCLUSION: Persons with advanced CKD have, independently of age, a much higher risk of cardiovascular mortality compared with the background population and in the age groups ˂70 years this is even more outspoken in persons with concomitant diabetes. These data highlight the importance of early cardiovascular risk assessment for this population.